Hackathons as a Tool for Solution Development: The Hackers do Bem Experience - Pereira, Lisandra R.; Nascimento, Felipe; Cordeiro, Kauane (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.12684, 2025)
This article reports on the experience of the 2nd Hackathon of the Hackers do Bem Program, aimed at developing cybersecurity skills through a practical and collaborative approach. The methodology combined Design Thinking with the ”From Zero to Hero”strategy, which promotes intensive and progressive training for participants with varying levels of knowledge. The event included workshops, mentoring sessions, and practical challenges based on real scenarios, fostering collaborative learning and the application of knowledge. The results indicate high engagement, technical advancement of participants, and the quality of the solutions developed. The study highlights the potential of immersive events for talent development and the strengthening of innovation.